Penerapan akuntabilitas dan transparansi pada pengelolaan dana bantuan operasional satuan pendidikan di SMP Spektrum Manado - Piri, Christian; Budiarso, Novi Swandari; Sardjono, Olivia Y. M. (Riset Akuntansi dan Portofolio Investasi, 2025)
This study aims to examine the implementation of accountability and transparency in managing the Operational School Assistance Fund (BOSP) at SMP Spektrum Manado. A qualitative approach with a case study design was employed, and data were collected through in-depth interviews with key informants, including the school principal, treasurer, and ARKAS operator. The findings indicate that the school has managed BOSP funds administratively in accordance with existing regulations, particularly in planning, reporting, and regulatory compliance. However, public participation in the formation of the BOSP Team and the dissemination of financial reports to the community has not been fully realized. Information regarding fund utilization remains confined within the internal system and is not openly shared through publicly accessible channels. Consequently, although formal accountability has been maintained, transparency to the public requires further improvement, particularly in terms of accessibility, clarity, and openness of information.